A Sovereign Currency Approach to China's Policy Options. Issue 3 (3rd May 2016) - Liu, Xinhua; Wray, L. Randall
Abstract : This article examines the fiscal and monetary policy options available to China as a sovereign currency-issuing nation operating in a dollar standard world. We first summarize a number of issues facing China, including the possibility of slower growth, global imbalances, and a number of domestic imbalances. We then analyze current monetary and fiscal policy formation and examine some policy recommendations that have been advanced to deal with current areas of concern. We next outline the sovereign currency approach and use it to analyze those concerns. We conclude with policy recommendations consistent with the policy space open to China.